Removal of microplastics from agricultural runoff using biochar: a column feasibility study - Olubusoye, Boluwatife S.; Cizdziel, James V.; Wontor, Kendall; Heinen, Edward; Grandberry, Tony; Bennett, Erin R.; Moore, Matthew T. (Frontiers in Environmental Science, 2024)
Plastics are extensively used in agriculture, but their weathering and degradation generates microplastics (MPs) that can be carried by runoff into water bodies where they can accumulate and impact wildlife. Due to its physicochemical properties, biochar has shown promise in mitigating contaminants in agricultural runoff. However, few studies have examined its effectiveness at removing MPs. In this study, we assessed MP pollution (>30 μm) in runoff from a farm in the Mississippi Delta and examined the effectiveness of biochar (pinewood and sugarcane) to remove MPs from aqueous solutions. Using micro-Fourier Transform Infrared spectroscopy (µ-FTIR), we observed an average of 237 MPs/L (range 27-609) in the runoff, with most particles identified as polyethylene, polyamide, polyvinyl chloride, polyurethane, acrylonitrile butadiene styrene, and polyarylamide. Biochar columns effectively removed MPs from runoff samples with reductions ranging from 86.6% to 92.6%. MPs of different sizes, shapes, and types were stained with Nile red dye (to facilitate observation by fluorescence) and quantified their downward progress with multiple column volumes of water and wet/dry cycles. Smaller MPs penetrated the columns further, but ≥90% of MPs were retained in the ~20 cm columns regardless of their shape, size, and type. We attribute these results to physical entrapment, hydrophobic behaviors, and electrostatic interactions. Overall, this proof-of-concept work